Exploring creativity management of design for additive manufacturing. Issue 4 (2nd October 2021) - Lindwall, Angelica; Wikberg Nilsson, Åsa
ABSTRACT: While many argue that Additive Manufacturing (AM) opens up new possibilities in design due to its higher degree of design freedom, it is also suggested that it can increase creativity in product design. It has been further proposed that creative outcomes are limited by the imagination of the designer: designers are often asked to take full advantage of the new design potentials given by AM, yet without having the supports that are needed to increase their creativity. Current literature focuses neither on supporting creative perspectives in Design for AM (DfAM) nor on how to manage the higher degree of design freedom that can be present. As a consequence of this noticeable gap in the literature, this paper continue to explore what areas that need to be considered in creativity management, to fully support designers in utilising their creative abilities in relation to AM in design. The paper proceeds through a literature study on creativity in DfAM and presents a case study with experienced designers who are just starting to work with AM in their design practices. This paper contributes to the field with the notion of a creativity layer laid upon DfAM, visualized by three characteristics of creativity (expertise, creative thinking skills and motivation) drawn from previous research. This results in three concrete propositions of areas that need to be considered in future research on how to include a creativity management perspective in DfAM.